Phytohormone-Based Regulation of Trichome Development - Li, Jinxing; Wang, Xingxing; Jiang, Rui; Dong, Boran; Fang, Shiyuan; Li, Qing; Lv, Zongyou; Chen, Wansheng (Frontiers in Plant Science, 2021)
Phytohormones affect plant growth and development. Many phytohormones are involved in the initiation of trichome development, which can help prevent damage from UV radiation and insect bites and produce fragrance, flavors, and compounds used as pharmaceuticals. Phytohormones promote the participation of transcription factors in the initiation of trichome development; for example, the transcription factors HDZIP, bHLH and MYB interact and form transcriptional complexes to regulate trichome development. Jasmonic acid (JA) mediates the progression of the endoreduplication cycle to increase the number of multicellular trichomes or trichome size. Moreover, there is crosstalk between phytohormones, and some phytohormones interact with each other to affect trichome development. Several new techniques, such as the CRISPR-Cas9 system and single-cell transcriptomics, are available for investigating gene function, determining the trajectory of individual trichome cells and elucidating the regulatory network underlying trichome cell lineages. This review discusses recent advances in the modulation of trichome development by phytohormones, emphasizes the differences and similarities between phytohormones initially present in trichomes and provides suggestions for future research.